Effect of stimulation frequency on osteogenic capability of electrical muscle stimulation - Shigeo M. TANAKA (Journal of Biomechanical Science and Engineering, 2014)
Exercise is effective as a preventive modality of osteoporosis because bone formation is accelerated by mechanical loading. However, elderly patients with osteoporosis are often difficult to exercise, which brings some risks of fractures during exercise with a fall. We focused on electrically-elicited muscle contraction to mechanically stimulate bone formation without any voluntary physical activities. The osteogenic effect of this method has been reported previously, however, it is unknown yet what the stimulation regimen is desirable to maximize the osteogenic effect. To provide basic knowledge to determine effective stimulation patterns in this method, this study aimed to investigate the effect of stimulation frequency on the osteogenic capability of electrical muscle stimulation in rats. The left quadriceps of rats were stimulated electrically for 30 min per day for 3 consecutive days under anesthesia. The stimulation waveform was a series of pulse trains composed of pulses with amplitude of 2 mA, 552 μs duration, and 50% duty ratio. The cyclic muscle contractions were generated by reversing the polarity of the electrical stimulation at 2, 10, 20, 40, or 80Hz. The stimulation effects were evaluated at the levels of gene expression and bone formation using RT-PCR and bone histomorphometry, respectively. Muscle stimulation at 20 Hz elicited a significantly higher expression level of osteocalcin mRNAs than those at the other frequencies. The 20-Hz stimulation also yielded the highest bone formation rate. However, these results did not correspond to the results of mechanical stimulation factors, including total number of contractions and average and cumulative muscle contraction forces during the stimulation period, suggesting a mechanism other than a dose-dependent effect of mechanical stimulation on osteogenesis. It was concluded that 20 Hz was the most effective frequency for eliciting the osteogenic effect of electric muscle stimulation in the rat. This finding provides useful information for establishing a stimulation regimen in clinical application of this method.